Family Healthcare Functions in Caring for Diabetic Ulcer Patients - Oktaviani, Nurul; Patimah, Iin; Awaludin, Aceng Ali (Karsa Husada Health Institute Garut, 2024)
Diabetic ulcers are the most common complication in type 2 diabetes mellitus. Diabetic ulcers are full-thickness wounds that frequently occur in specific parts of the body, particularly in the lower extremities. These wounds are a significant concern because they can lead to severe complications, including infections, amputations, and even reduced quality of life if not managed properly. Patients with diabetic ulcers require not only medical attention but also substantial support from their families in daily care and management. The family plays a crucial role in providing therapeutic health care to members suffering from diabetic ulcers. This includes ensuring proper wound care, helping patients adhere to prescribed treatment regimens, monitoring blood glucose levels, and supporting lifestyle changes such as a balanced diet and regular physical activity. However, the extent to which families can perform these roles effectively depends on their knowledge and caregiving abilities. The purpose of this study is to assess the knowledge and abilities of families in caring for family members with diabetic ulcers. This research is a quantitative descriptive study conducted with a sample of 37 respondents, selected using a total sampling technique. The study utilized a questionnaire that had been rigorously tested for validity and reliability to ensure the accuracy of the findings. The results of this study indicate that while the majority of families (59.5%) possess good knowledge about diabetic ulcers and their care, a significant proportion (64.9%) lack the ability to effectively care for family members with this condition. These findings highlight the need for targeted education and training programs to enhance the caregiving skills of families, enabling them to provide better support and improve outcomes for patients with diabetic ulcers.